Strengthening the Role of Youth in Promoting Religious Moderation through Social Media - Wijayanti, Tri Yuliana; Harlis, Syukri Alfauzi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
With the rapid development of technology, social media has become a vital tool in disseminating information, particularly among youth. This study aims to analyze and identify effective strategies to strengthen the role of youth in spreading religious moderation through social media. Using a descriptive-analytical method, this research identifies various strategies that can be implemented by youth to become agents of religious moderation. Data were collected through interviews with youth involved in youth organizations and through content analysis of popular social media platforms such as TikTok and Instagram. The results show that youth hold a strategic role in promoting religious moderation amidst an information overload that often leads to the spread of misinformation and intolerance. Strengthening digital literacy skills, including training as gatekeepers and influencers on social media, is crucial to ensure that youth can differentiate between accurate information and misinformation while effectively promoting moderation. Additionally, peacebuilding campaigns on social media have proven to be a significant step in enhancing youth’s role. In conclusion, youth have great potential as agents of religious moderation if equipped with digital skills and a deep understanding of moderation, contributing to the reduction of conflict-inducing misinformation